Solvent form : art and destruction - Pappas-Kelley, Jared (Manchester scholarship online, 2019)
This book is about the destruction of art, both in terms of objects that have been destroyed - lost in fires, floods or vandalism - and the general concept of art operating through object and form. Through re-examinations of such events as the Momart warehouse fire in 2004 and the activities of art thief Stephane Breitwieser, the book proposes an idea of solvent form hinging on the dual meaning in the words solvent and solvency, whereby art, while attempting to make secure or fixed, simultaneously undoes and destroys through its inception. Ultimately, the book questions what is it that may be perceived in the destruction of art and how we understand it, and further how it might be linked to a more general failure.